AN ANALYSIS OF FINAL TEST QUALITY ON EFL STUDENTS - Firman Ahmad Faizal; Syahban Mada Ali (Inspiring: English Education Journal, 2022)
The purpose of this research is to determine the quality of the final test in terms of difficulty level, discrimination leves, distractor effectiveness, validity, and reliability for senior high school students in second grade at SMA Negeri 3 Parepare. This research used a quantitative design with content analysis. The investigation was conducted at SMA Negeri 3 Parepare. The subject was 134 English final test form the second grade. However, the researcher took 58 students from three classes to serve as test subjects, with the sample for this research being retrieved utilizing a random selection group technique. They were XI MIPA 1, XI MIPA, and XI IPS 1. Based on the overall analysis of the 30 test items, it can be concluded that the final test for senior high school at the second grade SMA Negeri 3 Parepare was of medium difficulty (p), meaning that the test was neither too easy nor too tough. On the discrimination (D) scale, there were 6 (20%) items with outstanding classification, 1 (3,33%) item with adequate classification, and 23 (76,6%) items with good classification. Distractor effectiveness is likewise weak, since 12 (40%) of the items have very poor distractors. On the validity 9 (30%) items were invalid and need to be replaced. However, 21 (70%) items were valid. The final test for senior high school at the second grade SMA Negeri 3 Parepare is reliable since the reliability index 0,972, it was higher than the table value of critical of product moment it has shows that the final test was reliable.